Konsepsi Manajemen Perubahan - Anggraini, Siti (Universitas Prof. Dr. Moestopo (Beragama), 2008)
All institutions live and perform in two time periods: : today and tomorrow. Tomorrow is being made today-irevocably in most cases. In turbulent times managers can not assume that tomorrow will be an extensionof today. On the contrary, they must manage of